TOBACCO ABUSE EXPOSURE IN WOMEN AND ITS OUTCOMES TO PERINATAL AND CONGENITAL ANOMALIES IN NEWBORNS : A SYSTEMATIC REVIEW - Septia, Nindirah; Destian S, Ajeng; Hafdhah, Noratul; Hinaya Zalukhu, Corry Ida (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Pregnant women are at danger for tobacco smoke both actively and passively. Pregnant women are typically exposed to environmental tobacco smoke (ETS) in a variety of settings for varying durations of time. Cigarette smoke has a devastating effect on both pregnant women and the fetus. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 286 articles, whereas the results of our search on SagePub brought up 98 articles. The results of the search conducted for the last year of 2014 yielded a total 123 articles for PubMed and 6 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, tobacco smoking has an influence on pregnant women's immune, hormonal, and metabolic systems. The chemical contained in tobacco smoke has been linked to various pregnancy complications that result in poor pregnancy outcomes, including preterm birth, spontaneous abortion, and harmful effects on newborns. Infants may suffer from respiratory, behavioral, and neurological disorders, SIDS, and other congenital anomalies.The effect of tobacco smoke, actively or passively, is related with poor outcomes for pregnant mothers and their offspring.